Efficacy of cement stabilization for ultra-soft clay - Toh, Soon Kee (2018)
Offshore land reclamation has been a challenge for various reasons. Firstly, there is a lack of granular fill materials for land reclamation. Dredged clay slurry has been identified as an alternative reclamation material. However, dredged slurry has extremely high-water content, high compressibility and low shear strength. This suggests that the extremely soft fill must be treated to create a workable platform to accommodate the equipment for land reclamation works. This report hence aims to investigate the efficacy of cement stabilization for ultra-soft clay. The experiments were conducted using various cement content to stabilize soft clay slurry with a water content of twice its liquid limit. All specimens were cured for 7, 14, 28 and 56 days. Unconfined compressive strength (UCS) tests were carried to determine the compressive strength of all specimens. Other parameters including fluidity, bulk density, water content, specific gravity and porosity were also measured to complement the entire analysis. Microstructural analysis such as X-ray diffraction (XRD) and scanning electron microscopic (SEM) were also carried out to evaluate the micro fabric profile of cement treated soils. The results show that a relatively high cement content (≥ 160 kg/m3) should be used if aiming to achieve 28-day UCS higher than 100 kPa. However, there are a few limitations observed during the execution of the experiments and recommended suggestions are proposed.